Psychological Capital in Food Safety Social Co-governance - Chen, Xiujuan; Wu, Linhai (Frontiers in Psychology, 2019)
Social co-governance of food safety is an advocacy model to deal with current global food safety risks. Food safety co-governance involves the collaboration and partnership of government, industry, and society. The success of this collaboration is dependent on the construct of positive psychological capital. This paper discusses the concept of psychological capital and its four elements of self-efficacy, optimism, hope, and resiliency in line with co-governance in food safety. Accordingly, the paper proposes that great success in food safety co-governance would be realized if the government, industry, and society nurture positive psychological capital. Psychological capital can help corporates to instill organizational commitment on employees, thus promote food safety. Furthermore, positive psychological capital can help the government to appeal to the emotions of food companies and social actors to ensure self-efficacy toward food safety. The government can inspire hope by setting food safety goals and plans to achieve them, and a reward program will motivate food companies and promote self-efficacy in co-governance efforts. The government can also reinforce the efforts of companies in leveraging the elements of PsyCap in food safety, since the production of high-quality food is also dependent on the behaviors and attitudes of the workforce. Furthermore, the government can utilize social persuasion to improve the engagement of social actors in food safety regulations.